Presence of Newcastle disease virus in wild birds of a coastal wetland nearby Lima - Ventocilla W., Katrin (2011)
The present study evaluated the presence of the Newcastle Disease Virus in feces of wild birds inhabiting “El Paraiso” coastal wetland, located in the district of Huacho, Lima. Fresh fecal samples were collected from 942 wild birds of various species. The viral isolation was carried out by inoculating 10-day-old SPF embryonated eggs. Four isolates of Paramixovirus-1 (APMV-1), apparently the lentogenic type were obtained, showing that these birds were shedding the virus. This study represents the first in isolating APMV-1 in faeces from apparently healthy wild birds in Peru.